ANALISIS KINERJA KEUANGAN DAN KEMAMPUAN KEUANGAN PEMERINTAH DAERAH DALAM PELAKSANAAN OTONOMI DAERAH DI PROVINSI SULAWESI TENGGARA - Mustarim, Israwati; Rosnawintang, Rosnawintang; Akib, Mulyati (JPEP (Jurnal Progres Ekonomi Pembangunan), 2019)
This study aims to analyze financial performance and financial capacity in implementing regional autonomy. The object of this research is financial performance and financial capacity in the implementation of regional autonomy in 2011 to 2017. The data collection techniques of this study describe, analyze and interpret the financial performance and financial capabilities of the Regency / City government of Southeast Sulawesi Province which are measured by calculating financial ratios based on reports realization of APBD for fiscal year 2011-2017 and presented in writing in a systematic manner. The results of this study found that financial performance is still not financially independent and is in an innovative relationship pattern, where external parties are still very much needed in government administration, the effectiveness of PAD is very good and indirect expenditure activities in parent regions are allocated more than 50 percent, while for autonomous regions direct expenditure is allocated more than 50 percent, financial capability measured by the degree of fiscal autonomy is in the very low category but the financial ability index is very good.Â Keywords: Regional Autonomy, Financial Ability, Financial Performance